The study of effect on controlled release of iodine on bacterial biofilm eradication in wounds - Szuszkiewicz, Katarzyna Maria (Univerzita Pardubice, 2018)
The work deals with the determination of the influence of the kinetics of iodine release from wound care products containing iodine on the biofilm eradication. The kinetics of iodine release of commercial formulations and own-made wound dressings with two-component Iodine Generator were compared with the use of an in vitro starch gel model and subsequently with the use of sensors with platinum electrodes working in a biamperometric mode. The efficacy of bandages on biofilm eradication was checked using the modified Lubbock biofilm model that was prepared from the blend of following bacteria strains previously isolated from human chronic wounds: Staphylococcus aureus, Pseudomonas aeruginosa, Enterococcus faecalis, Escherichia coli and Streptococcus agalactiae.
Studium efektu řízeného uvolňovaní jódu na eradikaci bakteriálního biofilmu v ránách
Keywords: mikrobiální biofilm; jód; chronické rány; biamperometrie; tištěné platinové elektrody; microbial biofilm; iodine; chronic wounds; biamperometry; screen-printed platinum electrodes